Perceived service quality at higher education institutions: A study on the success factors of total quality management practices in Bangladesh - Md Mashiur Rahman; Salma Nasrin (Social Sciences and Humanities Open)
The Total Quality Management (TQM) approach has gained significant attention in the Higher Education (HE) sectors worldwide, originating in the United States in the mid-1980s to drive continuous improvement within higher education institutions (HEIs). While TQM has been widely embraced in developed nations to evaluate service quality in HEIs, its application in developing countries remains relatively unexplored and fragmented. This study aims to fill this gap by investigating students' perceived service quality in HEIs in Bangladesh using the TQM approach. Data collected from 384 respondents across four established public universities in Bangladesh were analyzed using partial least squares-structural equation modeling (PLS-SEM) and SmartPLS 3.0 software. The findings underscore significant barriers to service quality perception at HEIs in Bangladesh, including a deficient learning environment, ineffective student relationship management, student dissatisfaction, limited student involvement, and inadequate student focus. Therefore, addressing these challenges is crucial for policymakers and practitioners to maintain service quality standards and improve educational outcomes at HEIs in developing countries.